IMPLEMENTASI GRI DI INDONESIA: TANTANGAN DAN MANFAAT BAGI PERUSAHAAN - Muhammad Raihan Gutama; Ersi Sisdianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract : The implementation of the Global Reporting Initiative (GRI) in Indonesia has become an increasingly important issue in the context of corporate sustainability and non-financial reporting. GRI, which is an international standard for sustainability reporting, has become a reference for many global companies in communicating their social, economic, and environmental impacts to the public. In Indonesia, the implementation of GRI still faces significant challenges despite strong encouragement from the government and other stakeholders to improve transparency and accountability in business practices.This abstract aims to analyze the challenges and benefits faced by Indonesian companies in implementing the GRI standards. The main challenges faced include a lack of understanding and awareness of the importance of sustainability reporting, as well as obstacles in terms of limited resources and internal capacity of companies. In addition, many companies also have difficulty in integrating sustainability data and indicators into existing reporting systems, due to differences in standards and interpretations in measuring environmental, social, and economic impacts. Another obstacle is the lack of incentives or regulations that force companies to comply with the GRI standards in their entirety.However, despite these significant challenges, the implementation of GRI provides various benefits for companies in Indonesia. One of the main benefits is the improvement of the company's reputation in the eyes of consumers, investors, and other stakeholders who increasingly prioritize sustainability and corporate social responsibility. Transparent sustainability reporting through GRI also helps companies identify areas that need improvement, as well as encourage innovation and efficiency in the use of natural resources. In addition, companies that implement GRI well tend to find it easier to meet increasingly stringent government regulations related to the environment and social responsibility.This abstract will also discuss the importance of the role of government and related institutions in providing support for companies to overcome challenges in implementing GRI, as well as the need for increased collaboration between the public and private sectors in creating a better sustainability reporting ecosystem. With the increasing global attention to sustainability issues, it is hoped that the implementation of GRI in Indonesia can expand and make a positive contribution to sustainable development goals at the national and international levels. Keywords: GRI implementation, sustainability reporting, challenges and benefits, Indonesian companies, international standards, sustainability, regulations. Abstrak: Implementasi Global Reporting Initiative (GRI) di Indonesia menjadi isu yang semakin penting dalam konteks keberlanjutan perusahaan dan pelaporan non-keuangan. GRI, yang merupakan standar internasional untuk pelaporan keberlanjutan, telah menjadi acuan bagi banyak perusahaan global dalam mengomunikasikan dampak sosial, ekonomi, dan lingkungan mereka kepada publik. Di Indonesia, penerapan GRI masih menghadapi tantangan yang signifikan meskipun ada dorongan yang kuat dari pemerintah dan pemangku kepentingan lainnya untuk meningkatkan transparansi dan akuntabilitas dalam praktik bisnis. Abstrak ini bertujuan untuk menganalisis tantangan dan manfaat yang dihadapi oleh perusahaan-perusahaan Indonesia dalam mengimplementasikan standar GRI. Tantangan utama yang dihadapi termasuk kurangnya pemahaman dan kesadaran tentang pentingnya pelaporan keberlanjutan, serta hambatan dalam hal keterbatasan sumber daya dan kapasitas internal perusahaan. Selain itu, banyak perusahaan juga kesulitan dalam mengintegrasikan data dan indikator keberlanjutan dalam sistem pelaporan yang ada, karena adanya perbedaan standar dan interpretasi dalam pengukuran dampak lingkungan, sosial, dan ekonomi. Kendala lainnya adalah minimnya insentif atau regulasi yang memaksa perusahaan untuk mematuhi standar GRI secara menyeluruh. Namun, meskipun tantangan tersebut signifikan, implementasi GRI memberikan berbagai manfaat bagi perusahaan di Indonesia. Salah satu manfaat utama adalah peningkatan reputasi perusahaan di mata konsumen, investor, dan pemangku kepentingan lainnya yang semakin mengutamakan keberlanjutan dan tanggung jawab sosial perusahaan. Pelaporan keberlanjutan yang transparan melalui GRI juga membantu perusahaan dalam mengidentifikasi area-area yang memerlukan perbaikan, serta mendorong inovasi dan efisiensi dalam penggunaan sumber daya alam. Selain itu, perusahaan yang mengimplementasikan GRI dengan baik cenderung lebih mudah dalam memenuhi regulasi pemerintah yang semakin ketat terkait dengan lingkungan dan tanggung jawab social. Abstrak ini juga akan membahas pentingnya peran pemerintah dan lembaga terkait dalam memberikan dukungan bagi perusahaan untuk mengatasi tantangan dalam implementasi GRI, serta perlunya peningkatan kolaborasi antara sektor publik dan swasta dalam menciptakan ekosistem pelaporan keberlanjutan yang lebih baik. Dengan semakin berkembangnya perhatian global terhadap isu keberlanjutan, diharapkan implementasi GRI di Indonesia dapat semakin meluas dan memberikan kontribusi positif terhadap tujuan pembangunan berkelanjutan di tingkat nasional maupun internasional. Kata kunci: Implementasi GRI, pelaporan keberlanjutan, tantangan dan manfaat, perusahaan Indonesia, standar internasional, keberlanjutan, regulasi.